An Investigation of the Effect of the Addition of Tin to 5 %Pd/TiO2 for the Hydrogenation of Furfuryl Alcohol. Issue 14 (1st June 2015) - King, Gavin M.; Iqbal, Sarwat; Miedziak, Peter J.; Brett, Gemma L.; Kondrat, Simon A.; Yeo, Benjamin R.; Liu, Xi; Edwards, Jennifer K.; Morgan, David J.; Knight, David K.; Hutchings, Graham J.
Abstract The selective hydrogenation of furfuryl alcohol was investigated at room temperature by using supported palladium catalysts. The catalysts are very selective to the formation of 2‐methylfuran. Furthermore, the addition of tin to palladium showed similar catalytic activity, but was more selective to tetrahydrofurfuryl alcohol. Variation of the Sn/Pd ratio has shown a considerable and interesting effect on the selectivity pattern. Addition of a small amount of Sn (1 wt %) shifted the selectivity towards tetrahydrofurfuryl alcohol and methyltetrahydrofuran, which are ring‐saturated molecules. Increasing the tin ratio further decreased the catalytic activity and also showed very poor selectivity to either of these products.